Experimental Studies on the Effect of Antenna Orientations to the Performance of OFDM-based System - J. Muslimin; A. L. Asnawi; A. F. Ismail; A. Z. Jusoh; N. A. Malek; H. A. M. Ramli (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Software-defined radio (SDR) is an emerging and promising high re-configurable platform for rapid prototyping inreal environment applications. It offers both flexibility and low cost to facilitate the development process of agile communication system, such as Orthogonal Frequency Division Multiplexing (OFDM). Other than modulation and transmission technique like OFDM, antenna orientations play a significant importance in wireless communication. The availabililty of SDR platform like USRP has enabled the empirical evaluation of antenna orientation to the system performance. The performance has been evaluated in terms of throughput and packet error rate. The findings show the antenna orientation affect the system performance significantly.